The Rise of a New Superpower Turkey's Key Role in the World Economy and Energy Market - Arcuri, Angelo; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2013)
The book explains the reasons for the recent economic success of Turkey by examining the transformation of the private sector and the development policies implemented by the Turkish government. Further concrete insights are provided by professionals working for institutional and business players such as SACE, the first Italian insurance group in the field of export credit, and ABIGEM, a business center supporting SMEs in Turkey. Turkish Airlines, winner of the Best Airline in Europe award in 2012, also contributed to the volume through useful information provided by its press office. Turkey’s strategic role in the energy market is then analyzed, with discussion of the limits and opportunities of the oil, gas, and renewable sectors. In addition, careful attention is paid to the difficult relations between Turkey and the European Union and to Turkey’s application for EU membership. Turkey is one of the most important emerging countries in the world thanks to the booming economic growth that has been achieved there during the past decade. This book analyzes the increasingly key role played by Turkey within the international community by focusing on two main issues: the economic scenario and the energy market.
1 Introduction -- 2 Economic Scenario -- 3 Energy Market -- 4 Relations with Europe.
Keywords: International economics; Globalization; Markets; Energy policy; Energy and state; Economic policy; Environmental economics; Law—Europe.; International Economics; Emerging Markets/Globalization.; Energy Policy, Economics and Management; Economic Policy; Environmental Economics; European Law